SMART VILLAGE DATA GOVERNANCE: SUBSIDIARITY PRINCIPLES VS DIGITAL CORPORATE EXPLOITATION - Ismaniah; Amalia Syauket; Tyastuti Sri Lestari (POLITEKNIK LP3I JAKARTA, 2026)
This study examines the administrative-legal challenges faced by digitalized village governments under Indonesia’s Personal Data Protection (PDP) Law. Utilizing a qualitative socio-legal approach with desk-based and digital ethnography methods, this research uses Panggungharjo Village—a national pinnacle model for Smart Villages—as its locus. The findings reveal a critical legal gap: while the central government mandates rigid, centralized data controller responsibilities on village administrations, rural areas face severe technological and financial constraints. Consequently, unchecked digital partnerships between Village-Owned Enterprises (BUMDes) and global tech corporations risk exposing citizens’ private data to surveillance capitalism. To bridge this gap, this paper argues that the constitutional principles of recognition and subsidiarity grant villages the sovereign authority to implement independent local governing strategies. This study formulates a novel administrative framework consisting of drafting data-governance village regulations, establishing community-based Data Protection Officers, and standardizing data-sharing agreements in BUMDes business contracts. By employing these localized legal instruments, digitalized villages can transform their inherent autonomy into a powerful shield to safeguard citizens' data without compromising rural independence in the global digital era.